M-LEARNING APPLICATION FOR COMPUTER NETWORKING SUBJECTS - Rahmalia Syahputri; Nurfiana Nurfiana; Ilham Fernando (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Nowadays, mobile application, called mobile learning, is widely used among academic staff to help them in the process of teaching and learning at university. This research proposed the use of mobile learning in computer network subjects, particularly computer network and security, to facilitate the ease of access to the source of material and evaluation. Based on the questionnaire that distributed to the students, 75% respondents found this application is easy to use, attractive, and helping them to understand the content of subjects.  KEY WORDS: Mobile learning, teaching media, networking subjects